An interesting case of extraluminal migrating fish bone - Rathod, Indutai G.; Pawar, Vishal H.; Shivasharan, Sujit M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Hypopharyngeal and oesophageal foreign bodies are usually intraluminal but sharp foreign bodies can get impacted submucosally or extraluminally due to inadvertent attempt of removal by patient. Foreign body impaction is a common condition in Asian populations, with fish bone being the most common, often migrating to the lateral neck space or related organs. This case report emphasizes the significance of proper history and awareness among clinicians about the migration of fish bones, aiming to prevent diagnosis delays and potential complications. The present case depicts an unusual presentation of fish bone in case of 71 year old male patient farmer by occupation presented with chief complains of difficulty in deglutition, right side diffuse neck swelling associated with foreign body sensation in throat. The patient underwent clinical and radiological examination, which was diagnostically confirmed that fish bone present in retropharyngeal space. In management we had done tracheotomy followed by endoscopic examination and SOS removal but foreign body not found intraluminally. Patient started on higher antibiotics to decrease septic foci. Patient improved drastically and managed the patient conservatively. To our knowledge such a case has not been reported in literature.